The Development of Spatial–Temporal, Probability, and Covariation Information to Infer Continuous Causal Processes - Dündar-Coecke, Selma; Tolmie, Andrew; Schlottmann, Anne (Frontiers in Psychology, 2021)
This paper considers how 5- to 11-year-olds’ verbal reasoning about the causality underlying extended, dynamic natural processes links to various facets of their statistical thinking. Such continuous processes typically do not provide perceptually distinct causes and effect, and previous work suggests that spatial-temporal analysis, the ability to analyse spatial configurations that change over time, is a crucial predictor of reasoning about causal mechanism in such situations. Work in the Humean tradition to causality has long emphasise on the importance of statistical thinking for inferring causal links between distinct cause and effect events, but here we assess whether this is also viable for causal thinking about continuous processes. Controlling for verbal and nonverbal ability, two studies (N=107; N=124) administered a battery of covariation, probability, spatial-temporal and causal measures. Results indicated that spatial-temporal analysis was the best predictor of causal thinking across both studies, but statistical thinking supported and informed spatial temporal analysis: covariation assessment potentially assists with identification of variables, while simple probability judgment potentially assists with thinking about unseen mechanisms. We conclude that the ability to find out patterns in data is even more widely important for causal analysis than commonly assumed, from childhood, having a role to play not just when causally linking already distinct events, but also when analysing the causal process underlying extended dynamic events without perceptually distinct components.